Seismic-Perturbed Obliquity Change as a Discrete Trigger Mechanism of El Niño and La Niña Episodes - Paul C. Rivera (MO.RI Publishing, 2022)
The global climate disruptor El Niño Southern Oscillation (ENSO) is difficult to forecast some years in advance due to lack of understanding of its root cause. An alternative physical mechanism is hereby proposed to describe the nature and sustaining force, and predict the occurrence of El Niño and La Niña phenomena. This is based on the earthquake-perturbed obliquity change model previously proposed as a major mechanism of the global climate change problem. Massive quakes can impart a very strong oceanic force that can move the moon which in turn pulls the earth’s axis and change the planetary obliquity. Analysis of the annual geomagnetic north-pole shift and global seismic data revealed this previously undiscovered force. Using a higher obliquity and constant greenhouse gas forcing in the global climate model EdGCM showed that the seismic-induced polar motion and associated enhanced obliquity could be the major mechanism governing the mysterious climate anomalies attributed to El Nino and La Nina cycles. The apparent eastward migration of high SST in the Pacific and the warming of the Indian and Atlantic Oceans south of the equator during ENSO years were correctly simulated by the model. The annual time series of global surface temperatures computed by EdGCM was compared with the observed global temperature and the results showed relatively good agreement. In addition, the heat wave that occurred in Europe during the summer of 2003 and the Russian heat wave of 2010 that killed over 55,000 people appeared to have been correctly simulated with higher obliquity. This study can help affected countries in water shortage contingency planning, disaster mitigation and may help prevent adverse economic and commercial impacts due to ENSO.